2010
DOI: 10.1673/031.010.11501
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the Mealybug,Phenacoccus solenopsison Cotton in the Laboratory

Abstract: Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) has been the current topic of research for insect taxonomists and applied entomologists in India due to its invasiveness, rapid spread, morphological and biological variations and the need for establishing an effective control strategy. The biology of the mealybug P. solenopsis was studied on cotton under laboratory conditions between August and October of 2009 with mean temperature and relative humidity of 23.3–30.2°C and 40.5–92.5% RH, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 6 publications
9
57
2
2
Order By: Relevance
“…Similar observations reported by Nikam et al, (2010) and Vennila et al, (2010). Newly emerged crawlers were light yellow in colour (Plate 2), light red eyes, three pairs of legs and a pair of seven segmented filiform antennae as observed under microscope.…”
Section: Nymphsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar observations reported by Nikam et al, (2010) and Vennila et al, (2010). Newly emerged crawlers were light yellow in colour (Plate 2), light red eyes, three pairs of legs and a pair of seven segmented filiform antennae as observed under microscope.…”
Section: Nymphsupporting
confidence: 89%
“…The present finding is in concurrence with the results of Nikam et al, (2010) and Vennila et al, (2010) who observed male cocoon after third molt and reported that sex differentiation could be difficult in third instar and in disagreement with the report of Hodgson et al, (2008) who observed the male cocoon after second moult.…”
Section: Nymphsupporting
confidence: 85%
See 2 more Smart Citations
“…In a bad infestation, their honeydew induces the development of sooty mold fungus (Saeed et al, 2007). This species has been recognized as an aggressively invasive species of agricultural and ornamental plants in China. P. solenopsis in the fields is difficult to manage (Ram and Saini, 2010;Vennila et al, 2010;Huang J et al, 2012;Zhou et al, 2012) for the following reasons: 1) this species possesses a waxy coating that protects it from insecticides and natural mortality factors, 2) P. solenopsis can also hide in soil cracks and crevices, 3) P. solenopsis exhibits a high reproductive rate and produces serious overlapping generations, and 4) the higher foraging tempo of ants provides additional effective protection for P. solenopsis. P. solenopsis cannot be controlled effectively; the losses in cotton yield in 2008 or 2009 were 1.4 × 10 6 t in China, 1.12 × 10 6 t in India, and 0.48 × 10 6 t in Pakistan (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%